Reliability and validity of the Chinese post-discharge coping difficulty scale-parent form in parents of premature infants: a multicenter cross-sectional study - Liu, Jin; Gong, Jingjing; Shen, Qingqing; Si, Zaixia; Gao, Jianli; Xu, Leijie; Liu, Xiaoqin; Song, Yayun; Li, Minmin (Frontiers in Psychology, 2023)
Background The measurement of the coping difficulties of parents of premature infants after discharge provides objective data for nurses to prepare infants for discharge. However, no Chinese scale has been developed to measure parents’ coping difficulties after their premature infants are discharged. Aim To translate the parent version of the Post-Discharge Coping Difficulty Scale (Ped-PDCDS) from English to Chinese and test the reliability and validity of the Chinese version in parents of premature infants. Methods A multicenter cross-sectional study of 356 parents of premature infants was conducted. The scale was symmetrically translated. Validity was evaluated in terms of content, construct, discriminant, and convergent validities. Reliability was assessed in terms of internal consistency, split-half reliability, and test–retest reliability. Results The Chinese Ped-PDCDS finally contained 11 items. Exploratory and confirmatory factor analyses results showed that the Chinese Ped-PDCDS had three dimensions, and the convergent and discriminant validities of the scale was satisfactory. The overall reliability, split-half reliability, and test–retest reliability of the scale was 0.85, 0.92, and 0.84, respectively. Conclusion The Chinese Ped-PDCDS has adequate psychometric properties, and is an easy and appropriate instrument for measuring parents’ difficulty in coping with premature infants.